Case Report: Effect of providing penalty kicking tendencies on goalkeeper's motor behaviour and performance: a case study with an on-field intervention on youth football - Luis-del Campo, Vicente; Esteves, Pedro Tiago; Monteiro, Leonardo Palma; Casanova, Filipe Luis Martins (Frontiers in Sports and Active Living, 2024)
The penalty kick is a crucial action in a football match that may determine the final outcome. It features a direct interaction between the shooter and goalkeeper where both search for relevant information as a means to achieve their respective performance goals. A case study, composed of an on-field intervention, was designed to analyze the influence of providing in advance penalty kicking tendencies of the shooters on a youth goalkeeping movement onset and saving performance. Data collection took place over 8 training sessions where a U10 young low-skilled, male goalkeeper and shooters were subjected to a penalty-kick shootout task. In each session, the goalkeeper faced a set of 10 penalty kicks recorded by a high-speed HD camera which allowed to calculate the moment that the shooter hit the ball and the goalkeeper movement onset in the direction of ball trajectory. Results showed that the goalkeeper delayed response initiation in the retention phase, when compared to the baseline and training phases, by moving closer to the foot-to-ball contact time by the penalty shooter. From this study, it can be highlighted that goalkeeping saving actions were adapted to the provision of a priori information about shooter kicking tendencies, to sustain a higher performance of the young goalkeeper during the penalty duelling.